Design and Analysis of a Spatial 3-DOF Parallel Manipulator with 2T1R-Type. (3rd May 2013) - Zhang, Yanbin; Ting, Kwun-Lon
Abstract A novel asymmetrical spatial parallel manipulator with three degrees of freedom is proposed. The moving platform of the manipulator has two-translational and one-rotational (2T1R) DOFs with respect to the fixed base. Two other manipulators with platforms with high rotational ability are obtained by making simple changes to the original manipulator's architecture. The platform of the new mechanisms can rotate 360 degrees around their axis. The motion output characteristics and the mobility of the manipulator are analyzed based on the screw theory. Solutions for position and pose, velocity, acceleration are derived. The Jacobian matrix, mapping the input velocity vector space into the output velocity vector space, is an identical matrix, so the parallel mechanism is free-singularity and fully-isotropic. Therefore, these manipulators perform very well with regard to motion and force transmission and have potential applications in the field of industrial robots and medical devices.